Nanocrystal electrode with electrocatalytic and photocatalytic activity

Nanocrystal electrode prepared by unbalanced flame aerosol method and plasma directional explosion method solves the problems of low catalytic activity and poor stability in photocatalytic and electrocatalytic technologies, and achieves efficient water pollutant removal and long-life electrode performance , provides more reliable deep treatment technology for wastewater.

CN119285033AActive Publication Date: 2025-01-10BEIJING NORMAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411411835.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The existing photocatalytic and electrocatalytic technologies have problems such as low catalytic activity, poor stability, low efficiency and high operating costs in water pollution control. Especially when dealing with a variety of pollutants in complex water bodies, the technology is adaptable and reliable. Insufficient sex.

Method used

The non-equilibrium flame aerosol method and plasma directional explosion method were used to prepare nanocrystalline electrodes with electrocatalytic and photocatalytic activities. The stability and catalytic properties of the electrode were enhanced through high-entropy ceramic layers and multi-element mixtures, preventing chloride ions from being penetrated, and Improve the mechanical strength and chemical stability of the electrode through synergistic action of specific metal elements.

Benefits of technology

It improves the material utilization rate of nanocrystal electrodes, reduces secondary pollution, enhances the stability and catalytic performance of the electrodes, extends the service life, and maintains efficient pollutant removal capabilities in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285033A_ABST
    Figure CN119285033A_ABST
Patent Text Reader

Abstract

The invention discloses a nanocrystal electrode with both electro-catalysis activity and photocatalytic activity. The preparation method comprises the following steps: firstly, polishing the titanium substrate, and soaking the titanium substrate in alkali liquor and oxalic acid; preparing an intermediate layer by adopting a non-equilibrium flame aerosol method, and forming a high-entropy ceramic layer on the surface of the titanium plate by setting parameters such as specific radio frequency power and carrier gas; a specific mixture is prepared and subjected to ball milling and other treatment to serve as a surface active layer starting material, the surface active layer is prepared through a plasma directional explosion method, and the steps are repeated and parameters are adjusted to improve compactness; and finally carrying out annealing treatment. The novel nanocrystal electrode has the characteristics of ultra-stable chloride ion penetration resistance, high mechanical strength, good conductivity, stability and uniformity and outstanding electro-catalysis and photocatalytic performance, and a new solution is provided for the field of advanced treatment of industrial sewage and wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

1. Technical Field

[0001] The present invention relates to the technical field of environmental pollution control, and in particular to a nanocrystalline electrode having both electrocatalytic and photocatalytic activities and a preparation method thereof. 2. Background Technology

[0002] Existing technologies in the field of water pollution control include physical methods such as precipitation and filtration, which can remove large-particle impurities but have limited effects on soluble pollutants; biological methods rely on microbial metabolism, have a long treatment cycle and are sensitive to toxic substances. Chemical methods such as flocculation and precipitation are prone to secondary pollution. Electrochemical and photochemical technologies have significant advantages in water pollution control. Electrochemical technology can directly degrade pollutants through electrochemical reactions. It is simple to operate, has a fast reaction speed, and can treat a variety of difficult-to-degrade organic matter. Photochemical technology uses light energy to excite the production of strong oxidizing substances, has a high efficiency in removing organic pollutants, and has no risk of secondary pollution. Both can effectively remove low-concentration, difficult-to-degrade pollutants in the deep treatment of sewage and wastewater. They have the characteristics of high efficiency, energy saving, and environmental protection, providing a new and effective way for water pollution control.

[0003] Photochemical water pollution control technology primarily utilizes light energy to stimulate chemical reactions to remove pollutants from water. Photocatalysis is a core method. The basic principle is that photocatalysts generate electron-hole pairs under illumination. The electrons react with dissolved oxygen in water to form strong oxidizing species such as superoxide radicals, while the holes react with water or hydroxide ions to form hydroxyl radicals. These active species oxidize and decompose organic pollutants, converting them into harmless substances. The advantages of photocatalytic technology include: high efficiency and environmental friendliness, the ability to utilize solar energy, and zero secondary pollution; wide applicability, and the ability to degrade a wide range of organic pollutants; and mild reaction conditions, operating at room temperature and pressure. However, this technology also has some disadvantages. Regarding catalytic activity, current photocatalysts have limited utilization of sunlight, resulting in low quantum efficiency. Regarding stability, photocatalysts may experience photocorrosion and aggregation over long periods of use, reducing their activity and stability. Regarding the efficiency of flat-plate photocatalysts, the limited light-receiving area results in low mass transfer efficiency, resulting in relatively low overall treatment efficiency.

[0004] Electrochemical water pollution control technology utilizes electrochemical reactions to treat pollutants in water. The basic principle is to apply a voltage across electrodes, causing pollutants in the water to undergo redox reactions on the electrode surface or in the solution, thereby removing or converting the pollutants. Electrocatalysis is a key method for this purpose. Its advantages include: rapid reaction speed, which can be controlled by adjusting parameters such as voltage and current; a wide range of applications, capable of treating a wide range of pollutants; and relatively simple equipment and easy operation. However, it also has some disadvantages. The catalytic activity of current electrocatalysts still needs to be improved, and their effectiveness in treating some difficult-to-degrade pollutants is limited. Regarding stability, electrocatalysts may be affected by corrosion and contamination over long-term operation, leading to a decrease in activity. Regarding electrocatalyst efficiency, the reactions on the electrode surface may be affected by factors such as mass transfer limitations and side reactions, resulting in actual efficiencies lower than theoretical values. Furthermore, the electrocatalytic process can consume significant amounts of electricity, resulting in high operating costs.

[0005] In the field of water pollution control, photocatalysis and electrocatalysis technologies have broad future development directions. On the one hand, it is necessary to develop higher-performance photocatalysts and electrocatalysts to improve catalytic activity, stability and efficiency. For photocatalysis, efforts should be made to improve the utilization rate of visible light and design new nanostructured catalysts to increase the specific surface area and active sites. For electrocatalysis, new electrode materials and structures should be explored to reduce overpotential and improve current efficiency. However, in current technical research, there are few mature technologies that organically combine photocatalysis and electrocatalysis. The photoelectrocatalytic technology, which is currently being studied more in the laboratory stage, is essentially also a photocatalytic technology. It uses the bias provided by the electric field to enhance the electron transfer process in the photocatalytic process. Therefore, it cannot avoid some of the essential defects of photocatalytic technology. In particular, for the synergistic removal of multiple pollutants in complex water bodies, the adaptability and reliability of the technology need to be improved. 3. Summary of the Invention

[0006] The present invention is made in view of the problems existing in the prior art. In the deep treatment of sewage and wastewater, although photocatalysis and electrocatalysis have certain effects, they have many defects. In terms of photocatalysis, the catalytic activity is limited by the low utilization rate of sunlight, especially the visible light part, and the quantum efficiency is low; the stability is poor, and photocorrosion and agglomeration are prone to occur; the flat-plate photocatalyst is inefficient, and the light-receiving area and mass transfer efficiency are limited. In terms of electrocatalysis, the catalytic activity is not ideal for the treatment of difficult-to-degrade pollutants; the stability is easily reduced by corrosion and pollution; the efficiency is affected by mass transfer limitations and side reactions, the actual efficiency is low and the operating cost is high. Nanocrystalline electrodes that have both electrocatalytic and photocatalytic activities have significant advantages. They have a large specific surface area and rich active sites, which can enhance the adsorption and degradation capabilities of pollutants and have higher stability. However, the preparation of nanocrystalline electrodes faces some technical obstacles. For example: it is extremely challenging to accurately control the size and morphology of nanocrystals, and the influence of different parameters on activity is complex, making it difficult to optimize performance. It is difficult to ensure the uniformity of nanocrystal loading on the electrode surface, which can easily lead to local activity differences. The preparation process is complex, requiring strict control of parameters such as temperature, atmosphere, and solution concentration, which not only increases the difficulty but also increases the cost. Furthermore, the synthesis methods and growth mechanisms of nanocrystals require further research to achieve efficient and controllable preparation and provide more reliable technical support for advanced wastewater treatment.

[0007] Furthermore, when nanocrystalline electrodes are used as photoelectrocatalytic anode materials, the penetration of chloride ions in wastewater can easily cause the coating to fall off, posing a stability risk. To address this issue, we discovered that a multi-element composite coating can be prepared using a non-equilibrium flame aerosol method. First, the combination of multiple elements can produce a synergistic effect, enhancing the stability and corrosion resistance of the coating. Tin can improve the conductivity and adhesion of the coating; zirconium can provide oxidative stability; silicon helps to form a dense structure, blocking the penetration of chloride ions; calcium fluoride can enhance the hardness and wear resistance of the coating; and gadolinium chloride may give the coating special chemical stability. The formation of this high-entropy ceramic layer on the titanium substrate can effectively prevent chloride ion penetration and improve the service life and stability of the nanocrystalline electrode in harsh environments.

[0008] The traditional electroplating method of nanocrystal electrodes has many disadvantages, including low material utilization, serious secondary pollution, and uncontrolled nanocrystal growth, resulting in weak bonding and easy peeling. We found that using a multi-element mixture as the starting material for the surface active layer and adopting a plasma directional explosion method to prepare the active layer has significant technical advantages. First, this method can improve material utilization, reduce waste and secondary pollution. Second, plasma directional explosion can precisely control the growth of nanocrystals, making the active layer structure more uniform and stable. The addition of boron nitride can enhance the mechanical strength and chemical stability of the active layer. Metallic elements such as lead, titanium, manganese, and zinc work together to give the active layer rich catalytic active sites, thereby improving the electrocatalytic performance of the electrode. At the same time, this preparation method can enhance the bonding between the active layer and the intermediate layer, effectively prevent peeling, and extend the service life of the electrode.

[0009] In order to achieve the above-mentioned object, the technical solution of the present invention is a nanocrystalline electrode having both electrocatalytic and photocatalytic activities, characterized in that its preparation method comprises the following steps:

[0010] Step 1: Select a titanium substrate with a purity of not less than 99.9%, first use wire cutting to cut the titanium substrate, select 200-400 mesh coarse sandpaper to polish the titanium substrate until it is smooth, then select 800 mesh or higher fine sandpaper to polish and remove the oxide layer on the surface of the substrate, soak the polished titanium substrate in a boiling sodium hydroxide solution with a mass concentration of 5% for 0.5 hours, then soak it in a boiling solution containing 1% mass concentration of oxalic acid for 2 hours, and then soak it in a 0.1% mass concentration of oxalic acid solution for use to prevent secondary oxidation of the titanium substrate;

[0011] Step 2: The nanocrystalline electrode intermediate layer is prepared by a non-equilibrium flame aerosol method. The titanium plate pretreated in step 1 is washed with deionized water and blown dry with nitrogen. The plate is then placed in the center of a non-equilibrium flame aerosol synthesis reactor. The non-equilibrium flame aerosol equipment is set to a radio frequency of 3 MHz, a power of 45 kW, argon as the carrier gas, with a flow rate of 30 standard liters / minute, and a sheath gas of equal volumes of argon and hydrogen, with a flow rate of 120 standard liters / minute.

[0012] Step 3: A mixture of metallic tin, zirconium nitrate, elemental silicon, calcium fluoride, and gadolinium chloride in a mass ratio of 17:3:2:1:0.02 is prepared, crushed by ball milling to a particle size of less than 200 nanometers and thoroughly mixed, continuously fed through a vibrating powder feeder, and transported to the injection nozzle of a non-equilibrium flame aerosol reactor via argon carrier gas, and continuously and evenly sprayed onto the surface of the titanium plate. The powder mixture is fed at a feed rate of approximately 1.2 to 2.0 g / min. During the synthesis process, the reactor pressure is maintained at 66.7 kPa and the temperature is maintained at 1200° C. The reaction is continued for 200 seconds to obtain a titanium substrate having a high-entropy ceramic layer with ultra-stable chloride ion penetration resistance;

[0013] Step 4: preparing a mixture of boron nitride, lead, titanium, manganese, and zinc in a mass ratio of 120:28:19:2:1 as a starting material for the surfactant layer, placing the mixture in n-heptane, and ball milling under argon for 40 hours to obtain mixed nanoparticles with a particle size of less than 50 nanometers;

[0014] Step 5: The surface active layer of the nanocrystal electrode is prepared by a plasma directional explosion method. The titanium substrate with the high-entropy ceramic layer obtained in step 3 is placed in the center of the spark plasma sintering equipment. The hybrid nanoparticles obtained in step 4 are sputtered at high speed on the surface of the titanium substrate under argon gas transport. At the same time, a pulsed DC electric field with a voltage of 1.2 kilovolts, a period of 100 milliseconds, and a duty cycle of 5:1 is applied to both sides of the substrate. Since metal lead, titanium, manganese, zinc, etc. are all active metals, a sintering reaction can occur during the sputtering process, forming a surface active layer with high mechanical strength, good electrical conductivity, stable and uniformity, and a similar expansion rate with the high-entropy ceramic layer on the surface of the titanium substrate. The reaction is continued for 10 seconds and then stopped;

[0015] Step 6: Perform a secondary plasma directional explosion step, adjust the pulse DC voltage to 0.8 kV, the period to 10 milliseconds, and the duty cycle to 5:1 to improve the density of the surfactant layer, and continue the reaction for 5 seconds before stopping;

[0016] Step 7, repeating steps 5 and 6 again in sequence, repeating the operation 3 to 5 times, to obtain a titanium substrate with a surface active layer having a multi-level stable structure;

[0017] Step 8, annealing treatment, annealing the titanium substrate with a surface active layer with a multi-level stable structure obtained in step 7 at 350°C in a vacuum atmosphere of 0.1 to 1 Pa to further optimize the crystal structure and surface chemical state of the material, improve the electrocatalytic and photocatalytic properties of the electrode, and finally obtain a nanocrystalline electrode with both electrocatalytic and photocatalytic activity.

[0018] The present invention is beneficial in that:

[0019] 1) Improve material utilization and reduce pollution: Compared with traditional electrodeposition, the new method can improve material utilization, reduce waste and secondary pollution, and is more environmentally friendly.

[0020] 2) Precise control of nanocrystal growth: The plasma directional explosion method can precisely control the growth of nanocrystals, making the active layer structure uniform and stable, and avoiding the problem of uncontrolled nanocrystal growth in traditional methods.

[0021] 3) Enhanced bonding and catalytic performance: Using a specific mixture as the starting material strengthens the bonding between the active layer and the intermediate layer, preventing peeling and extending the life of the electrode. At the same time, multiple metal elements synergistically provide abundant catalytic active sites, improving electrocatalytic performance.

[0022] 4) Enhanced corrosion resistance and stability: The high-entropy ceramic layer prepared by the non-equilibrium flame aerosol method can effectively prevent the penetration of chloride ions, enhance the stability and corrosion resistance of the electrode in harsh environments, and provide reliable technical support for fields such as deep treatment of sewage and wastewater. IV. Description of the Figures

[0023] In order to more clearly illustrate the specific embodiments of the present invention, the following briefly describes the drawings used in the description of the specific embodiments. Figure 1 Schematic diagram of a non-equilibrium flame aerosol reactor, wherein the reference numerals are described as follows:

[0024] 1-Vibrating powder feeder; 2-High-pressure argon cylinder; 3-RF controller; 4-Feeding pipeline; 5-Injection nozzle; 6-Sample tray; 7-Rotating base. Figure 2 Figures characterizing nanocrystalline electrodes with both electrocatalytic and photocatalytic activity. Figure a is a scanning electron micrograph of a nanocrystalline electrode prepared by conventional electrodeposition; Figure b is a scanning electron micrograph of a nanocrystalline electrode prepared by nonequilibrium flame aerosol and plasma directed explosion methods; Figures c and d are X-ray diffraction patterns of the nanocrystalline electrode with both electrocatalytic and photocatalytic activity before and after a 1000-hour intensive lifespan test.

[0025] Figure 3 When landfill leachate is treated by the method of the present invention, the concentration of the original solution (calculated as the chemical oxygen demand value) changes over time under the conditions of blank, electricity, light, and photoelectricity.

[0026] Figure 4 When fracturing flowback fluid is treated by the method of the present invention, the concentration of the original solution (calculated as chemical oxygen demand) changes over time under the conditions of blank, electricity, light, and photoelectricity. V. Specific Implementation Methods

[0027] The present invention is described in detail below with reference to the accompanying drawings and embodiments:

[0028] Example 1:

[0029] A nanocrystalline electrode having both electrocatalytic and photocatalytic activities, the preparation method of which comprises the following steps: firstly selecting a titanium substrate with a purity of not less than 99.9%, firstly cutting the titanium substrate by wire cutting, selecting 200-400 mesh coarse sandpaper to grind the titanium substrate to be smooth, then selecting 800 mesh or higher fine sandpaper to polish and remove the oxide layer on the surface of the substrate, soaking the polished titanium substrate in a boiling sodium hydroxide solution with a mass concentration of 5% for 0.5 hour, soaking it in a boiling solution containing 1% mass concentration of oxalic acid for 2 hours after cleaning, and then soaking it in a 0.1% mass concentration of oxalic acid solution for standby use to prevent secondary oxidation of the Ti substrate; the intermediate layer of the nanocrystalline electrode is prepared by a non-equilibrium flame aerosol method, and the pretreated titanium plate is subjected to a After washing with deionized water and drying with nitrogen, the mixture was placed in the center of a non-equilibrium flame aerosol synthesis reactor. The non-equilibrium flame aerosol device was set to a radio frequency of 3 MHz, a power of 45 kW, argon as the carrier gas, a flow rate of 30 standard liters / minute, and a sheath gas of equal volumes of argon and hydrogen, with a flow rate of 120 standard liters / minute. A mixture of metallic tin, zirconium nitrate, elemental silicon, calcium fluoride, and gadolinium chloride in a mass ratio of 17:3:2:1:0.02 was prepared, ball-milled to a particle size of less than 200 nanometers and thoroughly mixed. The mixture was continuously fed through a vibrating powder feeder and transported to the injection nozzle of the non-equilibrium flame aerosol reactor via argon carrier gas and continuously and evenly sprayed onto the surface of the titanium plate (a schematic diagram of the non-equilibrium flame aerosol reactor is shown in the attached figure). Figure 1As shown), the feed rate of the powder mixture is set to be about 1.2 to 2.0 g / min. During the synthesis process, the reactor pressure is maintained at 66.7 kPa and the temperature is maintained at 1200°C. After the reaction lasts for 200 seconds, a titanium substrate with a high entropy ceramic layer having ultra-stable anti-chloride ion penetration ability is obtained; a mixture of boron nitride, metal lead, metal titanium, metal manganese, and metal zinc with a mass ratio of 120:28:19:2:1 is configured as the starting material for the surface active layer, the mixture is placed in n-heptane, and under argon protection, ball milled for 40 hours to obtain mixed nanoparticles with a particle size of less than 50 nanometers; the surface active layer of the nanocrystalline electrode is prepared by a plasma directional explosion method, the titanium substrate with a high entropy ceramic layer obtained in step 3 is placed in the center of the spark plasma sintering equipment, and the mixed nanoparticles obtained in step 4 can be sputtered at a high speed on the surface of the titanium substrate under argon delivery, and a voltage of 1.2 kV is applied on both sides of the substrate, the cycle is 100 milliseconds, and the duty cycle is 100 milliseconds. A pulsed DC electric field of 5:1 is used. Since metal lead, titanium, manganese, zinc, etc. are all active metals, they can undergo sintering reactions during the sputtering process to form a surface active layer with high mechanical strength, good electrical conductivity, stable uniformity, and similar expansion rate with the high entropy ceramic layer on the surface of the titanium substrate. The reaction is continued for 10 seconds and then stopped; a secondary plasma directional explosion step is performed, and the pulsed DC voltage is adjusted to 0.8 kV, the period is 10 milliseconds, and the duty cycle is 5:1 to improve the density of the surface active layer. The reaction is continued for 5 seconds and then stopped; the operation is repeated 3 to 5 times in sequence to obtain a titanium substrate with a surface active layer with a multi-level stable structure; annealing treatment is performed, and the titanium substrate with a surface active layer with a multi-level stable structure is annealed at 350°C in a vacuum atmosphere of 0.1 to 1 Pa to further optimize the crystal structure and surface chemical state of the material, improve the electrocatalytic and photocatalytic properties of the electrode, and finally obtain a nanocrystalline electrode with both electrocatalytic and photocatalytic activity.

[0030] The scanning electron microscope image of the obtained nanocrystalline electrode is shown in the attached figure. Figure 2 The surface structure of the nanocrystalline electrode prepared by this method is more compact, while in contrast, the nanocrystalline electrode structure prepared by the traditional electrodeposition method (see Appendix Figure 2 a) It is relatively rough and has many cracks on the surface, which can easily lead to structural instability and coating peeling.

[0031] Example 2:

[0032] The nanocrystalline electrode with both electrocatalytic and photocatalytic activity obtained in Example 1 was subjected to an accelerated life test to examine the electrode's resistance to chloride ion penetration. Accelerated life test conditions: 1 M hydrochloric acid, 60°C, current density 1 A cm -2 , the plate spacing is 10mm, and the accelerated life test cycle is 1000 hours.

[0033] The results are as attached Figure 2As shown in c and d, it can be seen that after 1000 hours of enhanced life test, the crystal structure of the electrode surface has not changed significantly, proving that it has a strong ability to resist chloride ion penetration. At the same time, no obvious coating peeling was observed.

[0034] Example 3:

[0035] The nanocrystalline electrodes, prepared in this invention and possessing both electrocatalytic and photocatalytic activity, were used to treat landfill leachate collected from a landfill. The leachate had an initial chemical oxygen demand (COD) concentration of 350 mg / L, an ammonia nitrogen concentration of 120 mg / L, and a chloride ion concentration of 12,000 mg / L. The wastewater was treated in the presence of light, electricity, and photoelectricity.

[0036] The reactor is made of organic glass and has a volume of 30 (length) × 30 (width) × 50 (height) cm 3 The working electrode is a nanocrystalline electrode with both electrocatalytic and photocatalytic activity prepared by the method of the present invention, with an area of ​​30 (length) × 30 (width) cm 2, , placed on one side of the reactor, and the counter electrode, a stainless steel plate of the same size as the working electrode, was placed on the other side of the reactor. A 500W short-arc medium-pressure mercury lamp was used as the light source for the photochemical reaction, and an external quartz waterproof cover was placed in the middle of the reactor; a DC regulated power supply provided a constant current source for the electrochemical reaction, with a current density of 10 mA cm -2 The magnetic stirring rate was 1000 rpm. Sampling was performed regularly, and the chemical oxygen demand concentration in the water samples was determined using HJ828-2017 (Water Quality - Determination of Chemical Oxygen Demand - Potassium Dichromate Method). A simple photochemical performance test was performed with the light on and the power off; a simple electrochemical test was performed with the light off and the power on; and a photoelectric synchronous test was performed with the light on and the power on.

[0037] The reaction results are as follows Figure 3 As shown in the figure, in the blank experiment, there was no degradation of the leachate. Under the condition of only light, the removal efficiency of pollutants was low. After 60 minutes of treatment, the chemical oxygen demand concentration was only reduced by 56.8%. Under the condition of only constant current power supply, the chemical oxygen demand concentration was reduced by 69.3% after 60 minutes of treatment. When photoelectricity and light were present at the same time, the chemical oxygen demand concentration was reduced by 89.2% after 60 minutes of treatment.

[0038] Example 4:

[0039] Nanocrystalline electrodes with both electrocatalytic and photocatalytic activity, prepared in this invention, were used to treat fracturing flowback fluid collected from a shale gas operation site. The initial concentration (chemical oxygen demand) of the fracturing flowback fluid was 120 mg / L, the ammonia nitrogen concentration was 0.17 mg / L, and the chloride ion concentration was 8600 mg / L. The wastewater was treated in the presence of light, electricity, and photoelectricity.

[0040] The specific operation process is consistent with that in Example 3 and will not be repeated here. The reaction results are shown in the attached figure. Figure 4 As shown in the figure, in the blank experiment, the fracturing flowback fluid did not show any degradation. Under the condition of only light, the removal efficiency of pollutants was low. After 10 minutes of treatment, the chemical oxygen demand concentration decreased by 80%; under the condition of only constant current power supply, the chemical oxygen demand concentration decreased by 85.4% after 10 minutes of treatment; when photoelectricity was present at the same time, the chemical oxygen demand concentration decreased by 95.2% after 10 minutes of treatment, and almost complete degradation was achieved after 60 minutes of treatment.

[0041] The specific embodiments described above are only used to specifically illustrate the spirit of the present invention, and the scope of protection of the present invention is not limited thereto. For those skilled in the art, it is of course possible to easily make other embodiments by changing, replacing or modifying the technical contents disclosed in this specification, and these other embodiments should all be included in the scope of protection of the present invention.

Claims

1. A nanocrystalline electrode having both electrocatalytic and photocatalytic activities, characterized in that: The preparation method comprises the following steps: Step 1, select a titanium substrate with a purity of not less than 99.9%, first use wire cutting to cut the titanium substrate, use 200-400 mesh coarse sandpaper to grind the titanium substrate to smoothness, then use 800 mesh or more fine sandpaper to polish and remove the oxide layer on the surface of the substrate, put the polished titanium substrate into a boiling sodium hydroxide solution with a mass concentration of 5% and soak it for 0.5 hours, after washing, soak it in a boiling oxalic acid solution with a mass concentration of 1% for 2 hours, and then soak it in an oxalic acid solution with a mass concentration of 0.1% for standby use to prevent secondary oxidation of the titanium substrate; Step 2: The nanocrystalline electrode intermediate layer is prepared by a non-equilibrium flame aerosol method. The titanium substrate pretreated in step 1 is washed with deionized water and then dried with nitrogen. The substrate is placed in the center of a non-equilibrium flame aerosol synthesis reactor. The non-equilibrium flame aerosol device is set to have a radio frequency of 3 MHz, a power of 45 kW, argon as carrier gas, a flow rate of 30 standard liters / minute, and a sheath gas of equal volumes of argon and hydrogen, with a flow rate of 120 standard liters / minute. Step 3, preparing a mixture of metallic tin, zirconium nitrate, elemental silicon, calcium fluoride, and gadolinium chloride in a mass ratio of 17:3:2:1:0.02, crushing the mixture by ball milling to a particle size of less than 200 nanometers and fully mixing the mixture, continuously feeding the mixture through a vibrating powder feeder, and transporting the mixture to an injection nozzle of a non-equilibrium flame aerosol reactor through an argon carrier gas, and continuously and evenly spraying the mixture onto the surface of the titanium plate, setting the feed rate of the powder mixture to be about 1.2 to 2.0 g / min, maintaining the reactor pressure at 66.7 kPa and the temperature at 1200° C. during the synthesis process, and obtaining a titanium substrate having a high entropy ceramic layer with ultra-stable anti-chloride ion penetration capability after the reaction lasts for 200 seconds; Step 4, preparing a mixture of boron nitride, metal lead, metal titanium, metal manganese and metal zinc in a mass ratio of 120:28:19:2:1 as a starting material for the surfactant layer, placing the mixture in n-heptane, and ball milling for 40 hours under argon protection to obtain mixed nanoparticles with a particle size of less than 50 nanometers; Step 5, the surface active layer of the nanocrystalline electrode is prepared by a plasma directional explosion method, the titanium substrate with a high entropy ceramic layer obtained in step 3 is placed in the center of a spark plasma sintering device, the hybrid nanoparticles obtained in step 4 are sputtered at high speed on the surface of the titanium substrate under argon gas delivery, and a pulsed DC electric field with a voltage of 1.2 kilovolts, a period of 100 milliseconds, and a duty cycle of 5:1 is applied to both sides of the substrate. Since metal lead, metal titanium, metal manganese, metal zinc, etc. are all active metals, a sintering reaction can occur during the sputtering process to form a surface active layer with high mechanical strength, good electrical conductivity, stable and uniform, and similar expansion rate with the high entropy ceramic layer on the surface of the titanium substrate, and the reaction is stopped after 10 seconds; Step 6, performing a secondary plasma directional explosion step, adjusting the pulse DC voltage to 0.8 kV, the period to 10 milliseconds, and the duty cycle to 5:1 to improve the density of the surface active layer, and stopping after the reaction is continued for 5 seconds; Step 7, repeating steps 5 and 6 again in sequence, repeating the operation 3 to 5 times, to obtain a titanium substrate with a surface active layer having a multi-level stable structure; Step 8, annealing treatment, annealing the titanium substrate with a surface active layer with a multi-level stable structure obtained in step 7 at 350°C in a vacuum atmosphere of 0.1 to 1 Pa to further optimize the crystal structure and surface chemical state of the material, enhance the electrocatalytic and photocatalytic properties of the electrode, and finally obtain a nanocrystalline electrode with both electrocatalytic and photocatalytic activity.

Citation Information

Patent Citations

  • High-efficiency electrocatalytic oxidation electrode production process

    CN109626520A

  • Preparation method and application of electrode with high catalytic activity and stability

    CN112250229A